The Ins and Outs of Unemployment in the Long Run: Unemployment Flows and the Natural Rate - Murat Tasci (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper proposes an empirical method for estimating a long-run trend for the unemployment rate that is grounded in the modern theory of unemployment. I write down an unobserved components model and identify the cyclical and trend components of the underlying unemployment flows, which in turn imply a time varying estimate of the unemployment trend, the natural rate. I identify a sharp decline in the outflow rate - job finding rate - since 2000, which was partly offset by the secular decline in the inflow rate - separation rate - since 1980s, implying a relatively stable natural rate, currently at 6 percent. Numerical examples show that slower labor reallocation along with the weak output growth explains most of the persistence in unemployment since the Great Recession. Contrary to the business-cycle movements of the unemployment rate, a signi cant fraction of the low-frequency variation can be accounted for by changes in the trend of the inflows, especially prior to 1985. Finally, I highlight several desirable features of this natural rate concept that makes it a better measure than traditional counterparts. These include statistical precision, the significance of required revisions to past estimates with subsequent data additions, policy relevance and its tight link with the theory.
Keywords: E24; E32; J64; 330; unemployment; natural rate; unemployment flows; labor market search; Arbeitslosigkeit; Natürliche Arbeitslosenquote; Erwerbstätigkeit; Suchtheorie; Theorie